2007
DOI: 10.1055/s-2007-965438
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristic High Sulfate Content in Brassica oleracea is Controlled by the Expression and Activity of Sulfate Transporters

Abstract: The uptake and distribution of sulfate in BRASSICA OLERACEA, a species characterised by its high sulfate content in root and shoot, are coordinated and adjusted to the sulfur requirement for growth, even at external sulfate concentrations close to the K (m) value of the high-affinity sulfate transporters. Plants were able to grow normally and maintain a high sulfur content when grown at 5 or 10 microM sulfate in the root environment. Abundance of mRNAs for the high affinity sulfate transporters, BolSultr1;1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
60
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 40 publications
(61 reference statements)
13
60
0
Order By: Relevance
“…Besharati and Rastin (1999) also reported that S application had significant effects on root and shoot dry matter of maize grown in calcareous soils under greenhouse conditions. Total dry matter was not affected by low concentration of sulfate but affected when by the complete absence of S (Koralewska et al, 2007). The oxidation of S 0 resulted in both direct chemical changes through lowering soil pH, EC and increasing sulfate concentration.…”
Section: Discussionmentioning
confidence: 92%
“…Besharati and Rastin (1999) also reported that S application had significant effects on root and shoot dry matter of maize grown in calcareous soils under greenhouse conditions. Total dry matter was not affected by low concentration of sulfate but affected when by the complete absence of S (Koralewska et al, 2007). The oxidation of S 0 resulted in both direct chemical changes through lowering soil pH, EC and increasing sulfate concentration.…”
Section: Discussionmentioning
confidence: 92%
“…While in leaves of many species, sulfate constitutes about 50% of total sulfur, in others, such as Brassica oleracea, it can reach up to 90% (Durenkamp et al, 2007;Koralewska et al, 2007). Sulfate homeostasis is dependent on the interplay between supply and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…This sulfate can be remobilized through the action of group 4 sulfate transporters localized in the tonoplast and enter the assimilation pathway (Kataoka et al, 2004). The portion of sulfur stored as vacuolar sulfate is highly variable among environmental conditions and plant species but also between variants of the same species (Durenkamp et al, 2007;Koralewska et al, 2007;Loudet et al, 2007). Since the consequence of the high sulfate content is high demand for sulfate in the soil, leading to the need for sulfate fertilization, the control of plant sulfate homeostasis is of high interest.…”
mentioning
confidence: 99%
“…Previously, such high-affinity group 1 STs were characterized as being responsible for the primary uptake of sulfate by the root (Buchner et al, 2010). However, several studies also showed the presence of their transcripts in shoots of S-deficient plants, suggesting a further function for S distribution into different cell types in different tissues (Koralewska et al, 2007;Ciaffi et al, 2013). In contrast to what has been suggested before (Parmar et al, 2007;Koralewska et al, 2008), SlST1.1 and SlST1.2 showed the same pattern of regulation in both shoots and roots of tomato plants (Fig.…”
Section: Determination Of Metabolite Levelsmentioning
confidence: 99%